2012
DOI: 10.1188/12.cjon.e210-e220
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Family Caregivers and Challenges Faced in Caring for Patients With Lung Cancer

Abstract: Family caregivers (FCGs) of lung cancer patients face multiple challenges which impact their quality of life and well-being. Whether challenged physically, emotionally, socially or spiritually, distress in one area may compound challenges in other areas. In order to maintain function and health of FCGs as they provide valuable care for the health and well-being of the patient, attention must be given to the needs of FCGs for support and education. The purpose of this article is to describe the multifaceted cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 30 publications
2
33
0
1
Order By: Relevance
“…Similar to this study done by Pirragglia et al and Fujinami et al in US among caregivers of cancer patients showed high level of depression among the caregivers of terminally ill patients. 5,12 Kulkarni et al in Maharashtra, India and Carlsson et al in Sweden identified sleep problems among the caregivers of palliative patients and they found it was more among the younger age and women caregivers which was similar to this study. 7,9 In our study caregivers of conditions other than age related weakness, perceived high stress because the sudden diagnosis of the patient's illness was unexpected for their family and was not acceptable by the caregivers.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Similar to this study done by Pirragglia et al and Fujinami et al in US among caregivers of cancer patients showed high level of depression among the caregivers of terminally ill patients. 5,12 Kulkarni et al in Maharashtra, India and Carlsson et al in Sweden identified sleep problems among the caregivers of palliative patients and they found it was more among the younger age and women caregivers which was similar to this study. 7,9 In our study caregivers of conditions other than age related weakness, perceived high stress because the sudden diagnosis of the patient's illness was unexpected for their family and was not acceptable by the caregivers.…”
supporting
confidence: 80%
“…Study by Fujinami et al in United States showed financial constraints among caregivers due to loss of income, which was similar to this study. 12 Present study found financial issues caregivers of poor socioeconomic status and those who provided care for patients with illnesses like paralytic conditions, mild mental retardation, psychosis following head injury, CKD, cancer esophagus and chronic heart disease which was similar to findings observed in studies done by Covinsky et al among caregivers of palliative patients in Unites States and Kulkarni et al in India. 7,13 In our study three women caregivers who provided care for persons suffering from stigmatizing illness like mental health related illness experienced social issues like avoiding going out or avoiding attending festivals, lack of social support and lack of enough time to spend with their partners and children.…”
supporting
confidence: 80%
“…Researches reveal the need for a multi-professional team to prepare the caregiver and clarify the doubts related to the patient’s illness. This can be a way to reduce the caregiver’s anxiety and increase the quality of the care provided 9 , 34 . A clear communication with the family is fundamental, given that uncertainty regarding the disease process is one of the factors that most impairs the well-being of the caregiver 35 .…”
Section: Discussionmentioning
confidence: 99%
“…1 Previous studies have demonstrated that FCGs of cancer patients experience decreased quality of life (QOL) and psychological distress related to their caregiver role. 2 …”
Section: Introductionmentioning
confidence: 99%